Comparative study on views of Nursing students and nursing staff views about the ‎role of nursing staff in clinical teaching of nursing students in teaching hospitals ‎of Guilan University of Medical Science - shadman reza masouleh; moohamad eshagh moohamadi; saghi mousavi; yaser torabi; fariba asgari (Journal of Holistic Nursing and Midwifery)
Introduction: Clinical training is the most important part of nursing education, as it is called ‎the heart of nursing education. Many different factors influence nursing education. Evaluation ‎of nursing staff and nursing student views about nursing student clinical training is very ‎important.‎ Objective: This study aims to compare the students and staff nurses views about staff nurses ‎role in clinical training of nursing student.‎